1979
DOI: 10.1002/ijc.2910240522
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selective breeding on the incidence of melanomas in sinclair miniature swine

Abstract: The influence of selective breeding on the incidence of cutaneous melanomas was studied in the Sinclair miniature swine melanoma model. Evaluation of the results of a large breeding study that produced 349 live progeny indicated that the incidence of melanomas (54%) was highest i n newborn progeny derived from melanoma female x melanoma male (MFX MM) matings. Newborn progeny f r o m normal female x melanoma male ( N F x MM) and melanoma female x normal male ( M F x N M ) matings had incidences of 22% and 21% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 7 publications
0
29
0
1
Order By: Relevance
“…The Sinclair Miniature Pig Melanoma model was established in the 1970s by breeding melanoma-bearing pigs to establish a line with up to 70% incidence of melanoma (Hook et al, 1979;Tissot et al, 1987). Melanoma in Sinclair swine usually develops in utero or within the first 6 weeks of life (Gomez-Raya et al, 2007), with lesions varying from benign flat nevi to large, deeply invasive, exophytic tumors possessing characteristics of malignant tumors (Das Gupta et al, 1989) as well as some in vitro characteristics of benign neoplastic cells found in childhood tumors such as retinoblastoma or neuroblastoma that are of neural or neural crest tissue origin as are melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The Sinclair Miniature Pig Melanoma model was established in the 1970s by breeding melanoma-bearing pigs to establish a line with up to 70% incidence of melanoma (Hook et al, 1979;Tissot et al, 1987). Melanoma in Sinclair swine usually develops in utero or within the first 6 weeks of life (Gomez-Raya et al, 2007), with lesions varying from benign flat nevi to large, deeply invasive, exophytic tumors possessing characteristics of malignant tumors (Das Gupta et al, 1989) as well as some in vitro characteristics of benign neoplastic cells found in childhood tumors such as retinoblastoma or neuroblastoma that are of neural or neural crest tissue origin as are melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Familial aggregation of benign and malignant melanocytic skin tumours has been described, particularly in purebred miniature swine such as Sinclair (7,36,48), and Hormel swine (26), but also in Duroc-Jersey swine (35,39). Among the several crosses involved are Duroc x Slovak pigs (47), Munich-Troll x German Landrace (60) and Duroc x Iberian swine (23).…”
Section: --Genetic Factorsmentioning
confidence: 99%
“…Among the several crosses involved are Duroc x Slovak pigs (47), Munich-Troll x German Landrace (60) and Duroc x Iberian swine (23). The influence of selective breeding on the incidence of cutaneous melanomas was studied in Duroc-Jersey swine (62) and in the Sinclair miniature swine (36).…”
Section: --Genetic Factorsmentioning
confidence: 99%
See 2 more Smart Citations